Perceived Health Effects of Tramadol HCL Abuse among Youths in Andoni Local Government Area of Rivers State, Nigeria - Mboi, Stanley Samuel; Iyama, William Azuka; Ogbuehi, Desmond; Willy, Ngozi Dennis (European Journal of Applied Sciences, 2022)
This study investigated perceived health effects of tramadol HCL abuse among youths in Andoni Local Government Area in Rivers State, Nigeria. Five specific objectives, research questions and four null hypotheses were formulated and tested at 0.05 level of significance. A descriptive cross-sectional design was adopted with the population of one hundred and sixteen thousand, eight hundred and twenty six youths (116, 826). The sample size of six hundred (600) was estimated using Yaro Yamane’s formula. Multistage sampling techniques were adopted and questionnaire instrument titled “Perceived Effects of Tramadol Abuse Questionnaire (TETAQ). A reliability coefficient of 0.84 was high enough and was used for this study. The data was analyzed using the Statistical Package for Social Sciences (SPSS) version 25.0. The results of this study showed that there was high perceived health effect of tramadol abuse found on the research question items of mean values, 2.14±0.66; 2.23±0.75 and 2.13±0.1.00 respectively. It was concluded that there was high perceived health, psychological, social and socio-economic effects of tramadol abuse among youths in Andoni Local Government Area in Rivers State. It was recommended among others that government should make policies to stop the importation and distribution of illicit substances and drugs.